Expression of renin–angiotensin system (RAS) components in endometrial cancer. Issue 1 (January 2017) - Delforce, Sarah J; Lumbers, Eugenie R; Corbisier de Meaultsart, Celine; Wang, Yu; Proietto, Anthony; Otton, Geoffrey; Scurry, Jim; Verrills, Nicole M; Scott, Rodney J; Pringle, Kirsty G
Abstract : A dysfunctional endometrial renin–angiotensin system (RAS) could aid the growth and spread of endometrial cancer. To determine if the RAS is altered in endometrial cancer, we measured RAS gene expression and protein levels in 30 human formalin-fixed, paraffin-embedded (FFPE) endometrioid carcinomas and their adjacent endometrium. All components of the RAS were expressed in most tumours and in adjacent endometrium; mRNA levels of (pro)renin receptor ( ATP6AP2 ), angiotensin II type 1 receptor ( AGTR1 ), angiotensin-converting enzyme ( ACE1 ) and angiotensin-converting enzyme 2 ( ACE2 ) mRNA levels were greater in tumour tissue than adjacent non-cancerous endometrium ( P = 0.023, 0.008, 0.004 and 0.046, respectively). Prorenin, ATP6AP2, AGTR1, AGTR2 and ACE2 proteins were abundantly expressed in both cancerous and adjacent non-cancerous endometrium. Staining was most intense in cancerous glandular epithelium. One potential target of the endometrial RAS, transforming growth factor beta-1 ( TGFB1 ), which is essential for epithelial-to-mesenchymal transition, was also upregulated in endometrial cancer tissue ( P = 0.001). Interestingly, TGFB1 was strongly correlated with RAS expression and was upregulated in tumour tissue. This study is the first to characterise the mRNA and protein expression of all RAS components in cancerous and adjacent non-cancerous endometrium. The greater expression of ATP6AP2, AGTR1 and ACE1, key elements of the pro-angiogenic/proliferative arm of the RAS, suggests that the RAS plays a role in the growth and spread of endometrial cancer. Therefore, existing drugs that inhibit the RAS and which are used to treat hypertension may have potential as treatments for endometrial cancer.